1997
DOI: 10.1038/ki.1997.262
|View full text |Cite
|
Sign up to set email alerts
|

Histological prevalence of β2-microglobulin amyloidosis in hemodialysis: A prospective post-mortem study

Abstract: The histological prevalence of beta-2 microglobulin amyloidosis (A beta 2m) was evaluated in a prospective study of joint samples obtained at autopsy in 54 patients on hemodialysis (HD) for 2 to 163 (median 47) months, aged 20 to 80 (median 63) years at HD onset. Carpal tunnel syndrome surgery or radiological signs of A beta 2m were present in 2 and 4% of them, respectively. A control group of 34 patients without end-stage renal disease, autopsied during the same period was used as a reference. The 153 sampled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(93 citation statements)
references
References 14 publications
4
86
1
2
Order By: Relevance
“…However, a postmortem study showed that b 2 M amyloid deposition occurs in 21% of cases within 2 years and in 33% within 4 years after initiation of HD. 24 Although the significance of pathologically evident but Abbreviations: CaÂP, calcium-phosphorus product; HD, hemodialysis; HDL-C, high-density lipoprotein cholesterol; hs-CRP, high-sensitivity C-reactive protein; IMT, intima-media thickness; iPTH, intact parathyroid hormone; LDL-C, low-density lipoprotein cholesterol. clinically silent amyloid deposition is unclear, it is notable that in patients on HD, pathological distribution of b 2 M amyloid deposition was consistent with that of tissue calcification in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, a postmortem study showed that b 2 M amyloid deposition occurs in 21% of cases within 2 years and in 33% within 4 years after initiation of HD. 24 Although the significance of pathologically evident but Abbreviations: CaÂP, calcium-phosphorus product; HD, hemodialysis; HDL-C, high-density lipoprotein cholesterol; hs-CRP, high-sensitivity C-reactive protein; IMT, intima-media thickness; iPTH, intact parathyroid hormone; LDL-C, low-density lipoprotein cholesterol. clinically silent amyloid deposition is unclear, it is notable that in patients on HD, pathological distribution of b 2 M amyloid deposition was consistent with that of tissue calcification in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…21 A large-scale postmortem study showed amyloid deposition in sternoclavicular joint and in the knee in 21%, 33%, 50%, 90%, and 100% of patients receiving HD for <2 years, after 2-4 years, 4-7 years, 7-13 years, and >13 years, respectively. 2 As regards PD, there are little data about the rate of DRA because the dialysis vintage of patients on PD is usually not so prolonged as in HD and there are only a few studies comparing the prevalence of DRA in HD and PD. Accumulation of amyloid may occur more slowly in patients treated by CAPD because serum b2M levels are lower in patients treated by CAPD in comparison to patients on HD with low-flux membranes.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…2 The ameliorations in dialysis techniques grow survival rates of hemodialyzed patients and, as a consequence, the risk of DRA. 25 • Age of onset of HD treatment: It is considered as an independent risk factor.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different proteins and polypeptides can acquire the abnormal conformational changes that lead to amyloid formation, and at least 19 different proteins are now known to be involved in the generation of amyloid in vivo (1). In the case of dialysis-related amyloidosis the protein involved is ␤ 2 -microglobulin (␤ 2 m), 1 which aggregates as amyloid fibrils in joints and tissues in ϳ20% of patients with kidney failure within 2 years after the onset of hemodialysis treatment (2). This type of amyloidosis does not seem to require a mutated, processed, or chemically modified precursor protein.…”
mentioning
confidence: 99%